Investigation of structural properties of Pr-doped hydroxyapatites synthesized via an ultrasonic-assisted wet chemical method - Ateş, Tankut; Bulut, Niyazi; Kaygılı, Omer; Keser, Serhat (Niyazi BULUT, 2023)
In this study, the effects of the duration of ultrasonication for Pr-doped hydroxyapatite (HA) were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM) and Fourier transform infrared (FT-IR) analyses. 0.25at.%Pr-containing HA samples were prepared by the ultrasonic-assisted wet chemical route using different ultrasonication times of 0, 30, 60, 90, and 120 min. The formation of the HA phase was confirmed by the FT-IR and XRD data for each sample. The morphology was significantly affected by the duration of ultrasonication. Compared to the untreated sample, remarkable decreases in both the crystallite size and the crystallinity were observed with the duration of ultrasonication.
Keywords: Material Production Technologies; Malzeme Üretim Teknolojileri